STRATEGI DALAM MENINGKATKAN KINERJA KARYAWAN MENUJU INDUSTRI 5.0 DI PT. ISS INDONESIA MENGGUNAKAN METODE SWOT - Bulgani, Alfan; Amas Priatna, Isep (Journal of Research and Publication Innovation, 2024)
This research aims to determine the strategies for improving performance towards Industry 5.0 at PT ISS, located at the Head Office in Greater Jakarta, Graha ISS, Bintaro Support Center, JL. Jenderal Sudirman, Blok J No.3 Bintaro Jaya 1559, using the SWOT method. This research is based on the phenomenon of concern about the rapid advancement of future technology, analyzed through interviews with primary data from employees. The research concludes that the strategic position of PT ISS Indonesia in enhancing employee performance towards Industry 5.0 is in quadrant 1. The coordinates X, Y at the point (1.044; 1.015) indicate a very safe or aggressive position. From the IFAS, it can be concluded that the international brand strength has the highest total value of 0.735, and employee welfare is the highest weakness with a value of 0.735. From the EFAS, it can be concluded that innovation opportunities have the highest total value of 0.599, and the threat of technological transition to robots has the highest total value of 0.45. Thus, the researcher concludes that the SO strategy is highly impactful for the company's sustainability in improving employee performance towards Industry 5.0 at PT ISS Indonesia.